2012
DOI: 10.1308/003588412x13373405387771
|View full text |Cite
|
Sign up to set email alerts
|

Management of colorectal polyp cancers

Abstract: INTRODUCTIONManagement of malignant colorectal polyps is controversial. The options are resection or surveillance. Resection margin status is accepted as an independent predictor of adverse outcome. However, the rate of adverse outcome in polyps with a resection margin of <1mm has not been investigated.METHODSA retrospective search of the pathology database was undertaken. All polyp cancers were included. A single histopathologist reviewed all of the included polyp cancers. Polyps were divided into three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 18 publications
4
24
0
Order By: Relevance
“…Naqvi et al came to different conclusions and suggested that clear resection margins, even those with less than 1 mm of clearance, might be treated safely only with surveillance [19].…”
Section: Discussionmentioning
confidence: 99%
“…Naqvi et al came to different conclusions and suggested that clear resection margins, even those with less than 1 mm of clearance, might be treated safely only with surveillance [19].…”
Section: Discussionmentioning
confidence: 99%
“…Data beyond the end of the whiskers are outliers and plotted as points. resection as a definitive procedure for early CRC is predicated by several factors: the ability to obtain complete resection, well or moderately differentiated adenocarcinomas, pathological evaluation of the entire intact specimen and the absence of lymphovascular invasion and tumour budding [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. These parameters highlight the importance of the pathologist and microscopic evaluation of the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological assessment of the polypectomy specimen, from specimen handling to reporting, is therefore crucial to the decision-making about the best therapeutic option. Recommended pathology reporting guidelines include comment on: margin status, level/extent of invasion (Haggitt [3], Kikuchi [4] or Ueno [7] measurement), tumour differentiation, lymphovascular space invasion and tumour budding since these help the endoscopist and/or surgeon in polyp risk stratification [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. However, the use of these prognostic parameters is based on small studies and some of these have poor interobserver agreement [11,13,30].…”
Section: Discussionmentioning
confidence: 99%
“…Most authors claim that a clear resection margin is anywhere from 1 mm [13] (as this definition was used in our study) to 2 mm [2,14]. According to Naqvi et al, even those with a <1mm clearance of cancer cells can be treated with surveillance [15].…”
Section: Discussionmentioning
confidence: 86%
“…There were no severe complications of grade III-IV or surgical mortalities. The median length of hospital stay was 12 days (range, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%